Extraction of Enzymes from Four Fungi and Their Use to Improve the Nutritive Value of Groundnut Pod for Broiler Feeding - Lawal, T.E.; Iyayi, E.A.; Adeniyi, B.A.; Adaramoye, O.A. (International Journal of Poultry Science, 2010)
Enzymes were extracted from four fungi: Aspergillus niger, Trichoderma viride, Rhizopus stolonifer and Mucor mucedo. The purified enzyme extracts were used to degrade Groundnut Pod (GNP) in solid state. Undegraded GNP-, degraded GNP- and Roxazyme G2G-based diets were fed to starter and finisher broilers at the rates 70 and 100 g kg-1 of diet, respectively. There was a production of a broad spectrum of enzymes from the 4 fungi. Treatment of the GNP with the fungal enzyme extracts caused a more significant (p